2015-09-25T14:51:11+08:00

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
(x+y)(x+y) = x² + 2xy + y²

Using the FOIL Method
Multiply the first terms.
(x)(x) = x²

Multiply the first term of the first and last term of the second.
(x)(y) = xy

Multiply the last term of the first and first term of the second.
(y)(x) = xy

Lastly, multiply the last terms.
(y)(y) = y²

x² + xy + xy + y²

Add the like terms. (the like terms are underlined)
x² + xy + xy + y²
xy + xy = 2xy

x² + 2xy + y²
-KookEin
2015-09-25T15:50:09+08:00

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Multiply each term of the polynomial by the terms of another polynomial.

x · x = x²
x · y = xy
y · x = xy
y · y = y²

x² + xy + xy + y²
Combine like terms
x² + xy² + y²                      is the final answer